Design dan Implementasi Sistem Embedded Mikrokontroller ATMega8535 dengan Bahasa Basic - ISWANTO (Gava Media, 2008)
Design dan Implementasi Sistem Embedded Mikrokontroller ATMega8535 dengan Bahasa Basic